Public Awareness on Prevention Behavior of Coronavirus Disease-19 at North Sulawesi Indonesia - Tucunan, Ardiansa A.T.; Rumayar, Adisti A.; Ratag, Budi T.; Maitimo, Brigitte Inez (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The coronavirus diseases (COVID)-19 outbreak around the world has prompted the government to urge its citizens to take precautionary measures to minimize the incidence of COVID-19, which has been continued to attack the world, including Indonesia. The pandemic has led to a massive global public health campaign to slow the spread of the virus by increasing hand washing, reducing face touching, wearing masks in public, and physical distancing. AIM: This study aims to analyze the sociodemographic relationship of knowledge, attitudes, and practices of preventing COVID-19. METHOD: This study was an analytic survey with a cross-sectional study design, conducted for 3 months with number of samples 356 people spared across four districts and cities in North Sulawesi Province. There are two types of data collection those are through Google forms and face to face questions. The studied variables are sociodemography as independent variables and knowledge, attitude, and behavior of COVID-19 prevention. Data were analyzed with Chi-square test. RESULTS: The result of study, only gender has a relationship toward people’s attitudes toward COVID-19 prevention with p = 0.046; while most of the variables, namely, age (0.333), education (0.085), occupation (0.152), and income (0.966), did not have a significant relationship with attitudes toward the prevention of COVID-19. Gender has a relationship toward people’s attitudes toward COVID-19 prevention with p = 0.046; while most of the variables, namely, age (0.333), education (0.085), occupation (0.152), and income (0.966), did not have a significant relationship with attitudes toward the prevention of COVID-19. Most of the variables had a significant relationship with prevention measures, including age (0.008), education (0.009), and occupation (0.038); and only the gender variable (0.895) and monthly income (0.077) had no statistical relationship. CONCLUSION: It is important for the government and society to take a role by becoming more concerned about the COVID-19 pandemic through wise steps to prevent and protect public health using all available resources.